Implementation Of Learning Model "Local Toursm" Based Potential Of District Rembang - Eny Winaryati; Akhmad Fathurohman; Setia Iriyanto; Sri Haryani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract. The curriculum at all levels and types of education developed in accordance with the principle of diversification of educational unit, the potential of the area, and learners. This is the basis for learning model "Local Attractions" was developed. The core of this model is, to optimize the function and role of the local potential areas for improvement of the quality of learning. Implementation of the above model implemented in elementary, secondary, vocational and high school in Rembang district. The purpose of this study was to test the effectiveness of the model, based on the data a positive impact on the improvement of learning. The effectiveness of data obtained through assessment: student and teacher responses associated with the feasibility models, teaching observation, interviews andevaluation of the implementation of the model in the field. Results of the study data showed that the model effectivelyused.